POSS-based meso-/macroporous covalent networks: supporting and stabilizing Pd for Suzuki–Miyaura reaction at room temperature. Issue 62 (14th June 2016) - Zhang, Chenjun; Leng, Yan; Jiang, Pingping; Lu, Dan
Abstract : Porous covalent organic networks synthesized by Schiff base chemistry reaction of POSS and terephthalic aldehyde could serve as both supports and stabilizers for Pd catalyst, which exhibited excellent performances for Suzuki-Miyaura reactions. Abstract : A facile template-free strategy for the fabrication of organic–inorganic meso-/macroporous covalent networks was reported by the combination of the aminopropyl-polyhedral oligomeric silsesquioxanes (POSS) with terephthalic aldehyde (TPA) through Schiff base chemistry reactions. Such porous covalent networks have high BET surface areas and various abundant nitrogen-containing functionalities that could serve as both supports and stabilizers for homogeneous palladium (Pd) catalyst. The resulting heterogeneous Pd catalyst (Pd/POSS–TPAa ) exhibited enhanced catalytic activity for the Suzuki–Miyaura reactions at room temperature with a short reaction time, and the catalyst can be easily recycled up to five times without significant loss in the conversion and the leaching of Pd. The excellent performance of Pd/POSS–TPAa is mostly attributed to the strong coordination between N-containing groups in the covalent framework and Pd.